Environment-friendly modified starch-based biodegradable shopping bag and preparation method thereof
By adding calcium chloride, vitamin C and modified plastics to the modified starch-based biodegradable shopping bag, the problem of mechanical performance of modified starch-based biodegradable plastics in overheating and humid environments is solved, and the efficient degradation and weather resistance of shopping bags are achieved.
Patent Information
- Application Number
- CN202411747412.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-01
- Publication Date
- 2025-03-07
AI Technical Summary
The existing modified starch-based biodegradable plastics have reduced mechanical properties in overheating and humid environments, and are not completely degraded, breaking into small fragments, making it difficult to maintain performance in humid and high-temperature environments.
By adding calcium chloride, vitamin C, modified plastics, polylactic acid resin and other components to the modified starch-based biodegradable shopping bag, calcium chloride is used to promote the cross-linking reaction between starch molecules. Vitamin C provides antioxidant effects, and modified plastics and polylactic acid resins improve the weather resistance and mechanical properties of the materials.
It extends the service life of shopping bags, improves its mechanical properties and oxidation resistance in humid and high-temperature environments, and avoids the problems of oxidation damage and pigment accumulation of materials during long-term use.
Smart Images

Figure CN119570122A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to an environmentally friendly modified starch-based biodegradable shopping bag and a preparation method thereof. Background Art
[0002] Globally, the problem of disposable non-degradable plastic pollution is becoming increasingly serious. Countries have introduced policies to control it in order to promote the development and application of biodegradable plastics. As a new environmentally friendly material, biodegradable plastics have attracted global attention in recent years. They can be degraded into water, carbon dioxide and other inorganic substances by microorganisms in the natural environment, and will not cause long-term pollution to the environment. Compared with traditional plastics, they are more environmentally friendly and sustainable. With the rapid development of science and technology and the gradual enhancement of environmental awareness, the market demand for biodegradable plastics is growing, especially in the fields of packaging and agriculture. Modified starch biodegradable plastics have emerged as a new environmentally friendly material. Modified starch is based on natural starch, and new functional groups are introduced or the molecular structure is changed through physical, chemical or enzymatic treatment, so as to improve its performance and expand its application range. Modified starch biodegradable plastics not only inherit the renewable and degradable characteristics of natural starch, but also improve its processing performance and durability through modification. They are widely used in packaging, agriculture, medical and other fields, and have become one of the important ways to solve the problem of plastic pollution.
[0003] Existing modified starch-based biodegradable plastics have certain defects in performance. In practical applications, the performance of this type of plastic is somewhat different from that of traditional petroleum-based plastics. The mechanical properties of plastics are greatly reduced in overheated and humid environments. Although modified starch-based biodegradable plastics are designed to solve the problem of plastic pollution, they cannot currently be completely degraded and instead break into small pieces.
[0004] 1. Patent document CN103044718B discloses a starch-based biodegradable plastic and a preparation method thereof. The above patent achieves superiority over similar domestic products in terms of performance, biodegradability, price, etc. The research and development of this product has positive significance for alleviating "white pollution" and the shortage of petroleum resources, and has good economic and social benefits. However, the above patent cannot achieve the function of reducing the internal hydroxyl groups of starch molecules.
[0005] 2. Patent document CN111040392B discloses a starch-based biodegradable material and its preparation method and application. The above patent achieves low material cost, biodegradability, good film-forming performance, simple preparation, and suitability for industrial production and application. However, the above patent cannot achieve the strong antioxidant function of the environmentally friendly modified starch-based biodegradable shopping bag.
[0006] 3. Patent document CN112321903B discloses a process for producing biodegradable composite plastics. The above patent realizes a simple preparation process and is green and environmentally friendly. The biodegradable plastics produced have good flame retardancy, good weather resistance, and a tensile strength of up to 39.5 MPa. However, the above patent cannot achieve the function of reducing the stability of hydroxyl groups inside starch molecules.
[0007] 4. Patent document CN101914223B discloses a method for preparing a modified starch-polyvinyl alcohol-based composite plastic film. The above patent realizes a starch-based plastic film with good mechanical properties, water resistance and degradation properties, providing a very broad application prospect for starch-based plastic films. However, the above patent cannot realize the function of the modified plastic maintaining its performance in a humid and high temperature environment.
[0008] In summary, the above patents cannot achieve the function of reducing the internal hydroxyl groups of starch molecules, cannot achieve the function of strong antioxidant properties of environmentally friendly modified starch-based biodegradable shopping bags, cannot achieve the function of reducing the stability of the internal hydroxyl groups of starch molecules, and cannot achieve the function of maintaining the performance of modified plastics in humid and high-temperature environments, resulting in high difficulty in the reaction of the internal hydroxyl groups of starch molecules with metals and film formation, oxidation and destruction of the internal structure of shopping bags during long-term use, accumulation of pigments during production, high difficulty in starch processing and poor compatibility, and decreased mechanical properties and reduced service life in humid and high-temperature environments;
[0009] To this end, the present application proposes an environmentally friendly modified starch-based biodegradable shopping bag and a preparation method thereof, which can achieve the function of reducing the internal hydroxyl groups of starch molecules, achieving the strong antioxidant properties of the environmentally friendly modified starch-based biodegradable shopping bag, reducing the stability of the internal hydroxyl groups of starch molecules, and maintaining the performance of modified plastics in humid and high temperature environments. Summary of the invention
[0010] The object of the present invention is to provide an environmentally friendly modified starch-based biodegradable shopping bag and a preparation method thereof, so as to solve the technical problems proposed in the above background technology that the function of reducing the internal hydroxyl groups of starch molecules cannot be achieved, the function of strong antioxidant properties of the environmentally friendly modified starch-based biodegradable shopping bag cannot be achieved, the function of reducing the stability of the internal hydroxyl groups of starch molecules cannot be achieved, and the function of maintaining the performance of the modified plastic in a humid and high-temperature environment cannot be achieved, resulting in high difficulty in the reaction of the internal hydroxyl groups of starch molecules with metals and film formation, oxidation and destruction of the internal structure of the shopping bag during long-term use, accumulation of pigments during production, high difficulty in starch processing and poor compatibility, and decreased mechanical properties and reduced service life in a humid and high-temperature environment.
[0011] To achieve the above object, the present invention provides the following technical solution: an environmentally friendly modified starch-based biodegradable shopping bag and a preparation method thereof, comprising the following components in parts by weight: modified starch: 40 to 70 parts;
[0012] Modified plastics: 30 to 50 parts;
[0013] Polylactic acid resin: 20 to 40 parts;
[0014] Calcium chloride: 5 to 15 parts;
[0015] Vitamin C: 5 to 10 parts;
[0016] Plasticizer: 2 to 8 parts;
[0017] Acetylating agent: 0.5 to 3 parts;
[0018] Lubricant: 0.2 to 1 part;
[0019] The calcium chloride changes the thermodynamic parameters of starch gelatinization and reduces enthalpy change and entropy change through polarization phenomenon. The calcium ions in the calcium chloride form ionic bonds with hydroxyl groups in the modified starch to form a complex, which can promote the cross-linking reaction between starch molecules and increase the energy required to overcome the hydrogen bond between water molecules and salt ions during starch gelatinization.
[0020] Preferably, the modified starch comprises the following components in parts by weight: corn starch: 30 parts to 50 parts;
[0021] Hydrogen peroxide: 10 to 30 parts;
[0022] Amylase: 2 to 10 parts;
[0023] Glycerin: 2 to 6 parts;
[0024] Sodium hydroxide solution: 1 to 5 parts;
[0025] The oxygen atoms generated by the decomposition of hydrogen peroxide react with the hydroxyl groups in the corn starch molecules, converting the hydroxyl groups into carboxyl groups, aldehyde groups and ketone groups.
[0026] Preferably, the modified plastic comprises the following components in parts by weight: 20 to 35 parts of a copolymer of dibutyl adipate and butylene terephthalate;
[0027] Polybutylene succinate: 20 to 35 parts;
[0028] Polycaprolactone: 5 to 10 parts;
[0029] Glass fiber: 10 to 25 parts;
[0030] Wollastonite: 2 to 8 parts;
[0031] Graphite: 1 to 5 parts;
[0032] Coupling agent: 0.5 to 2 parts;
[0033] The glass fiber is short-cut glass fiber and long-cut glass fiber in a weight ratio of 3:1;
[0034] The coupling agent is a phthalate coupling agent and a silane coupling agent.
[0035] Preferably, the vitamin C can provide electrons to free radicals, interrupt the free radical chain reaction, slow down and hinder the oxidation process of the shopping bag. Vitamin C can clean and remove pigments during the production and processing of the shopping bag by neutralizing the free radicals.
[0036] Preferably, the weight ratio of the copolymer of dibutyl adipate and butylene terephthalate, polybutylene succinate and polycaprolactone is 5:3:2.
[0037] Preferably, the wollastonite has a unique needle-like fiber structure, which forms a fiber-reinforced effect during processing. The wollastonite can maintain stable physical and chemical properties at high temperatures. The wollastonite itself does not absorb water, and the thermal expansion absorption of wollastonite is small and the expansion is linear. Adding it to plastics can prevent the plastics from hygroscopic expansion and the generation of expansion cracks during the heat absorption of the plastics.
[0038] Preferably, the graphite is evenly distributed in the modified plastic, and the density of the graphite is 0.85-1.9 g / cm 3 The single-layer carbon atom plane of graphite and the layered structure of graphite can prevent the penetration of water molecules. The layered structure of graphite is combined with each other by the interaction of the instantaneous dipole moment of the molecular crystal. The force is weak, the structure is loose and it is easy to process.
[0039] Preferably, the preparation method of the modified starch is:
[0040] Step 1: Prepare enough corn starch and dry it in 70℃ environment for 2h;
[0041] Step 2: Add distilled water to prepare corn starch into starch emulsion;
[0042] Step 3: adding amylase at 60°C and pH=6.0 to enzymolyze the corn starch for 5 hours;
[0043] Step 4: adding sodium hydroxide solution to adjust the pH of the enzymatically hydrolyzed starch emulsion to 9.0 and stirring and soaking for 1 hour;
[0044] Step 5: Add hydrogen peroxide to the starch emulsion after adjusting the pH, and stir thoroughly;
[0045] Step 6: Filter and dry the product after the reaction to remove unreacted substances to obtain modified starch.
[0046] Preferably, the preparation method of the modified plastic is:
[0047] Step 1: prepare sufficient amounts of dibutyl adipate-butylene terephthalate copolymer, polybutylene succinate, polycaprolactone, glass fiber, wollastonite, graphite and coupling agent;
[0048] Step 2: Mix dibutyl adipate, butylene terephthalate copolymer, polybutylene succinate and polycaprolactone in a weight ratio of 5:3:2 and put them into a twin-screw extruder for mixing;
[0049] Step 3: Add glass fiber and wollastonite and mix for 2 hours;
[0050] Step 4: Add graphite and coupling agent and mix for 1.5 hours;
[0051] Step 5: obtaining the modified plastic through extrusion, cooling, pelletizing, washing and drying;
[0052] Step 6: Conduct quality inspection on the prepared plastic;
[0053] The temperatures in each zone of the twin-screw extruder (from the feed port to the die outlet) are 160°C, 200°C, 200°C, 220°C, 240°C, 200°C and 190°C.
[0054] Preferably, the preparation method of the environmentally friendly modified starch-based biodegradable plastic bag is:
[0055] Step 1: Prepare sufficient amounts of modified starch, modified plastic, polylactic acid resin, calcium chloride, vitamin C, plasticizer, acetyl agent and lubricant;
[0056] Step 2: Add appropriate amount of water and amylase to the modified starch, put it into a high-speed mixer, heat it to 80°C, and stir for 10 minutes;
[0057] Step 3: adding an acetylating agent to the gelatinized modified starch, and stirring at a stirring speed of 500 rpm for 20 minutes;
[0058] Step 4: Add plasticizer to the product after adding acetyl agent and stir for 15 minutes;
[0059] Step 5: Add lubricant to the mixture and stir for 30 minutes to obtain starch gel;
[0060] Step 6: Add modified plastic and polylactic acid resin and stir for 20 minutes;
[0061] Step 7: Put the uniformly mixed mixture into a twin-screw extruder for mixing;
[0062] Step 8: Add calcium chloride and vitamin C into a twin-screw extruder for mixing and extruding into granules;
[0063] Step 9: Put the prepared raw materials into a crusher and process them into small granular materials;
[0064] Step 10: Put the granular materials into the melting machine to melt the materials;
[0065] Step 11: Extruding the melted raw material into a film through an extruder;
[0066] Step 12: After cooling and solidification, a shopping bag is obtained;
[0067] The screw length-to-diameter ratio of the twin-screw extruder is 48:1, the screw speed is 300 rpm, the temperature of zone 1 is 90°C, the temperature of zone 2 is 120°C, the temperature of zone 3 is 135°C, the temperature of zone 4 is 120°C, and the temperature of zone 5 is 90°C.
[0068] Compared with the prior art, the present invention has the following beneficial effects:
[0069] 1. The present invention achieves the function of reducing the hydroxyl groups inside starch molecules by designing calcium chloride, solves the problem of the reaction between the hydroxyl groups inside starch molecules and metals and the high difficulty of film formation, can extend the service life of the environmentally friendly modified starch-based biodegradable shopping bag, and increase the mechanical properties and hydrophobic properties of the shopping bag;
[0070] 2. The present invention realizes the strong antioxidant function of the environmentally friendly modified starch-based biodegradable shopping bag by designing vitamin C, solves the problem of the internal structure of the shopping bag being damaged by oxidation during long-term use and the accumulation of pigments during production, can avoid the phenomenon of being unusable after a long period of time, increase the use time of the shopping bag, slow down the oxidation rate of the shopping bag, and enhance the stability and durability of the shopping bag;
[0071] 3. The present invention achieves the function of reducing the stability of the hydroxyl groups inside the starch molecules by designing modified starch, solves the problems of high difficulty in starch processing and poor compatibility, can reduce the interaction between starch molecules, and reduce the difficulty of starch in the blending process while retaining the green and degradable function;
[0072] 4. The present invention realizes the function of maintaining the performance of the modified plastic in a humid and high-temperature environment by designing the modified plastic, solves the problem of decreased mechanical properties and reduced service life in a humid and high-temperature environment, can improve the use experience of the shopping bag, reduce the phenomenon of shopping bags breaking during use, improve the quality of the shopping bags, and improve the economic benefits of the shopping bags. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 Schematic diagram of the preparation method of modified starch of the present invention;
[0074] Figure 2 It is a schematic diagram of the method for preparing modified plastics of the present invention;
[0075] Figure 3 This is a schematic diagram of the method for preparing the environmentally friendly modified starch-based biodegradable shopping bag of the present invention. DETAILED DESCRIPTION
[0076] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0077] Example 1
[0078] See also Figure 1 , Figure 2 and Figure 3 , an environmentally friendly modified starch-based biodegradable shopping bag, comprising the following components in parts by weight: modified starch: 50 parts;
[0079] Modified plastic: 40 parts;
[0080] Polylactic acid resin: 20 parts;
[0081] Calcium chloride: 5 parts;
[0082] Vitamin C: 5 parts;
[0083] Plasticizer: 3 parts;
[0084] Acetyl agent: 2 parts;
[0085] Lubricant: 0.5 parts;
[0086] The calcium chloride changes the thermodynamic parameters of starch gelatinization through polarization to reduce enthalpy change and entropy change. The calcium ions in the calcium chloride form ionic bonds with the hydroxyl groups in the modified starch to form a complex, which can promote the cross-linking reaction between starch molecules and increase the energy required to overcome the hydrogen bond between water molecules and salt ions during starch gelatinization.
[0087] The modified starch comprises the following components in parts by weight: 30 parts of corn starch;
[0088] Hydrogen peroxide: 120 parts;
[0089] Amylase: 7 parts;
[0090] Glycerin: 4 parts;
[0091] Sodium hydroxide solution: 2 parts;
[0092] The oxygen atoms generated by the decomposition of hydrogen peroxide react with hydroxyl groups in the corn starch molecules to convert the hydroxyl groups into carboxyl groups, aldehyde groups and ketone groups;
[0093] The modified plastic comprises the following components in parts by weight: 35 parts of a copolymer of dibutyl adipate and butylene terephthalate;
[0094] Polybutylene succinate: 20 parts;
[0095] Polycaprolactone: 10 parts;
[0096] Glass fiber: 15 parts;
[0097] Wollastonite: 2 parts;
[0098] Graphite: 3 parts;
[0099] Coupling agent: 1 part;
[0100] The glass fiber is short-cut glass fiber and long-cut glass fiber in a weight ratio of 3:1;
[0101] The coupling agent is a phthalate coupling agent and a silane coupling agent;
[0102] The vitamin C can provide electrons to free radicals, interrupt the free radical chain reaction, slow down and hinder the oxidation process of the shopping bag. The vitamin C can clean and remove pigments during the production and processing of the shopping bag by neutralizing the free radicals.
[0103] The weight ratio of the copolymer of dibutyl adipate and butylene terephthalate, polybutylene succinate and polycaprolactone is 5:3:2;
[0104] The wollastonite has a unique needle-like fiber structure, which forms a fiber-reinforced effect during processing. The wollastonite can maintain stable physical and chemical properties at high temperatures. The wollastonite itself does not absorb water, and the thermal expansion absorption of the wollastonite is small and the expansion is linear. When added to plastics, it can prevent the plastics from hygroscopic expansion and expansion cracks from occurring during the heat absorption process of the plastics.
[0105] The graphite is evenly distributed in the modified plastic, and the density of the graphite is 0.85-1.9 g / cm 3 The single-layer carbon atom surface of graphite and the layered structure of graphite can prevent the penetration of water molecules. The layers of the layered structure of graphite are combined by the interaction of the instantaneous dipole moment of the molecular crystal. The force is weak and the structure is loose, which is easy to process.
[0106] Further, prepare 5 parts of calcium chloride and 5 parts of vitamin C, and keep other material components unchanged;
[0107] Prepare a sufficient amount of corn starch and dry it at 70°C for 2 hours, add distilled water to adjust the corn starch into a starch emulsion, add amylase at 60°C and pH=6.0 to enzymolyze the corn starch for 5 hours, add sodium hydroxide solution to adjust the pH of the starch emulsion after enzymolysis to 9.0 and stir and soak for 1 hour, add hydrogen peroxide to the starch emulsion after adjusting the pH, stir it fully, filter and dry the product after the reaction to remove unreacted substances, and obtain modified starch;
[0108] Prepare sufficient amounts of dibutyl adipate and butylene terephthalate copolymer, polybutylene succinate, polycaprolactone, glass fiber, wollastonite, graphite and coupling agent, mix dibutyl adipate and butylene terephthalate copolymer, polybutylene succinate and polycaprolactone in a weight ratio of 5:3:2, put into a twin-screw extruder for mixing, add glass fiber and wollastonite, mix for 2 hours, add graphite and coupling agent, mix for 1.5 hours, obtain modified plastics through extrusion, cooling, pelletizing, washing and drying, and perform quality inspection on the prepared plastics, wherein the temperatures of each zone of the twin-screw extruder (from the feed port to the die outlet) are 160°C, 200°C, 200°C, 220°C, 240°C, 200°C and 190°C;
[0109] Prepare sufficient modified starch, modified plastic, polylactic acid resin, calcium chloride, vitamin C, plasticizer, acetylating agent and lubricant, add appropriate amount of water and amylase to the modified starch, put it in a high-speed mixer, heat it to 80°C, stir it for 10 minutes, add acetylating agent to the gelatinized modified starch, stir it for 20 minutes at a stirring speed of 500 rpm, add plasticizer to the product after the acetylating agent reaction, stir it for 15 minutes, add lubricant to the mixture, stir it for 30 minutes to obtain starch gel, add modified plastic and polylactic acid resin, stir it for 20 minutes, The uniformly mixed mixture is put into a twin-screw extruder for kneading, calcium chloride and vitamin C are added into the twin-screw extruder for kneading, extrusion granulation is performed, the prepared raw materials are put into a pulverizer, processed into granular small materials, the granular small materials are put into a melting machine, the small materials are melted, the melted raw materials are extruded into a film through an extruder, and after cooling and solidification, a shopping bag is obtained, wherein the screw length-diameter ratio of the twin-screw extruder is 48:1, the screw speed is 300 rpm, the temperature of the first zone is 90°C, the temperature of the second zone is 120°C, the temperature of the third zone is 135°C, the temperature of the fourth zone is 120°C, and the temperature of the fifth zone is 90°C.
[0110] Example 2
[0111] See also Figure 1 , Figure 2 and Figure 3 , an environmentally friendly modified starch-based biodegradable shopping bag, comprising the following components in parts by weight: modified starch: 50 parts;
[0112] Modified plastic: 40 parts;
[0113] Polylactic acid resin: 20 parts;
[0114] Calcium chloride: 5 parts;
[0115] Vitamin C: 5 parts;
[0116] Plasticizer: 3 parts;
[0117] Acetyl agent: 2 parts;
[0118] Lubricant: 0.5 parts;
[0119] The calcium chloride changes the thermodynamic parameters of starch gelatinization through polarization to reduce enthalpy change and entropy change. The calcium ions in the calcium chloride form ionic bonds with the hydroxyl groups in the modified starch to form a complex, which can promote the cross-linking reaction between starch molecules and increase the energy required to overcome the hydrogen bond between water molecules and salt ions during starch gelatinization.
[0120] The modified starch comprises the following components in parts by weight: 30 parts of corn starch;
[0121] Hydrogen peroxide: 120 parts;
[0122] Amylase: 7 parts;
[0123] Glycerin: 4 parts;
[0124] Sodium hydroxide solution: 2 parts;
[0125] The oxygen atoms generated by the decomposition of hydrogen peroxide react with hydroxyl groups in the corn starch molecules to convert the hydroxyl groups into carboxyl groups, aldehyde groups and ketone groups;
[0126] The modified plastic comprises the following components in parts by weight: 35 parts of a copolymer of dibutyl adipate and butylene terephthalate;
[0127] Polybutylene succinate: 20 parts;
[0128] Polycaprolactone: 10 parts;
[0129] Glass fiber: 15 parts;
[0130] Wollastonite: 2 parts;
[0131] Graphite: 3 parts;
[0132] Coupling agent: 1 part;
[0133] The glass fiber is short-cut glass fiber and long-cut glass fiber in a weight ratio of 3:1;
[0134] The coupling agent is a phthalate coupling agent and a silane coupling agent;
[0135] The vitamin C can provide electrons to free radicals, interrupt the free radical chain reaction, slow down and hinder the oxidation process of the shopping bag. The vitamin C can clean and remove pigments during the production and processing of the shopping bag by neutralizing the free radicals.
[0136] The weight ratio of the copolymer of dibutyl adipate and butylene terephthalate, polybutylene succinate and polycaprolactone is 5:3:2;
[0137] The wollastonite has a unique needle-like fiber structure, which forms a fiber-reinforced effect during processing. The wollastonite can maintain stable physical and chemical properties at high temperatures. The wollastonite itself does not absorb water, and the thermal expansion absorption of the wollastonite is small and the expansion is linear. When added to plastics, it can prevent the plastics from hygroscopic expansion and expansion cracks from occurring during the heat absorption process of the plastics.
[0138] The graphite is evenly distributed in the modified plastic, and the density of the graphite is 0.85-1.9 g / cm 3 The single-layer carbon atom surface of graphite and the layered structure of graphite can prevent the penetration of water molecules. The layers of the layered structure of graphite are combined by the interaction of the instantaneous dipole moment of the molecular crystal. The force is weak and the structure is loose, which is easy to process.
[0139] Further, prepare 10 parts of calcium chloride and 5 parts of vitamin C, and keep other material components unchanged;
[0140] Prepare a sufficient amount of corn starch and dry it at 70°C for 2 hours, add distilled water to adjust the corn starch into a starch emulsion, add amylase at 60°C and pH=6.0 to enzymolyze the corn starch for 5 hours, add sodium hydroxide solution to adjust the pH of the starch emulsion after enzymolysis to 9.0 and stir and soak for 1 hour, add hydrogen peroxide to the starch emulsion after adjusting the pH, stir it fully, filter and dry the product after the reaction to remove unreacted substances, and obtain modified starch;
[0141] Prepare sufficient amounts of dibutyl adipate and butylene terephthalate copolymer, polybutylene succinate, polycaprolactone, glass fiber, wollastonite, graphite and coupling agent, mix dibutyl adipate and butylene terephthalate copolymer, polybutylene succinate and polycaprolactone in a weight ratio of 5:3:2, put into a twin-screw extruder for mixing, add glass fiber and wollastonite, mix for 2 hours, add graphite and coupling agent, mix for 1.5 hours, obtain modified plastics through extrusion, cooling, pelletizing, washing and drying, and perform quality inspection on the prepared plastics, wherein the temperatures of each zone of the twin-screw extruder (from the feed port to the die outlet) are 160°C, 200°C, 200°C, 220°C, 240°C, 200°C and 190°C;
[0142] Prepare sufficient modified starch, modified plastic, polylactic acid resin, calcium chloride, vitamin C, plasticizer, acetylating agent and lubricant, add appropriate amount of water and amylase to the modified starch, put it in a high-speed mixer, heat it to 80°C, stir it for 10 minutes, add acetylating agent to the gelatinized modified starch, stir it for 20 minutes at a stirring speed of 500 rpm, add plasticizer to the product after the acetylating agent reaction, stir it for 15 minutes, add lubricant to the mixture, stir it for 30 minutes to obtain starch gel, add modified plastic and polylactic acid resin, stir it for 20 minutes, The uniformly mixed mixture is put into a twin-screw extruder for kneading, calcium chloride and vitamin C are added into the twin-screw extruder for kneading, extrusion granulation is performed, the prepared raw materials are put into a pulverizer, processed into granular small materials, the granular small materials are put into a melting machine, the small materials are melted, the melted raw materials are extruded into a film through an extruder, and after cooling and solidification, a shopping bag is obtained, wherein the screw length-diameter ratio of the twin-screw extruder is 48:1, the screw speed is 300 rpm, the temperature of the first zone is 90°C, the temperature of the second zone is 120°C, the temperature of the third zone is 135°C, the temperature of the fourth zone is 120°C, and the temperature of the fifth zone is 90°C.
[0143] Example 3
[0144] See also Figure 1 , Figure 2 and Figure 3 , an environmentally friendly modified starch-based biodegradable shopping bag, comprising the following components in parts by weight: modified starch: 50 parts;
[0145] Modified plastic: 40 parts;
[0146] Polylactic acid resin: 20 parts;
[0147] Calcium chloride: 5 parts;
[0148] Vitamin C: 5 parts;
[0149] Plasticizer: 3 parts;
[0150] Acetyl agent: 2 parts;
[0151] Lubricant: 0.5 parts;
[0152] The calcium chloride changes the thermodynamic parameters of starch gelatinization through polarization to reduce enthalpy change and entropy change. The calcium ions in the calcium chloride form ionic bonds with the hydroxyl groups in the modified starch to form a complex, which can promote the cross-linking reaction between starch molecules and increase the energy required to overcome the hydrogen bond between water molecules and salt ions during starch gelatinization.
[0153] The modified starch comprises the following components in parts by weight: 30 parts of corn starch;
[0154] Hydrogen peroxide: 120 parts;
[0155] Amylase: 7 parts;
[0156] Glycerin: 4 parts;
[0157] Sodium hydroxide solution: 2 parts;
[0158] The oxygen atoms generated by the decomposition of hydrogen peroxide react with hydroxyl groups in the corn starch molecules to convert the hydroxyl groups into carboxyl groups, aldehyde groups and ketone groups;
[0159] The modified plastic comprises the following components in parts by weight: 35 parts of a copolymer of dibutyl adipate and butylene terephthalate;
[0160] Polybutylene succinate: 20 parts;
[0161] Polycaprolactone: 10 parts;
[0162] Glass fiber: 15 parts;
[0163] Wollastonite: 2 parts;
[0164] Graphite: 3 parts;
[0165] Coupling agent: 1 part;
[0166] The glass fiber is short-cut glass fiber and long-cut glass fiber in a weight ratio of 3:1;
[0167] The coupling agent is a phthalate coupling agent and a silane coupling agent;
[0168] The vitamin C can provide electrons to free radicals, interrupt the free radical chain reaction, slow down and hinder the oxidation process of the shopping bag. The vitamin C can clean and remove pigments during the production and processing of the shopping bag by neutralizing the free radicals.
[0169] The weight ratio of the copolymer of dibutyl adipate and butylene terephthalate, polybutylene succinate and polycaprolactone is 5:3:2;
[0170] The wollastonite has a unique needle-like fiber structure, which forms a fiber-reinforced effect during processing. The wollastonite can maintain stable physical and chemical properties at high temperatures. The wollastonite itself does not absorb water, and the thermal expansion absorption of the wollastonite is small and the expansion is linear. When added to plastics, it can prevent the plastics from hygroscopic expansion and expansion cracks from occurring during the heat absorption process of the plastics.
[0171] The graphite is evenly distributed in the modified plastic, and the density of the graphite is 0.85-1.9 g / cm 3 The single-layer carbon atom surface of graphite and the layered structure of graphite can prevent the penetration of water molecules. The layers of the layered structure of graphite are combined by the interaction of the instantaneous dipole moment of the molecular crystal. The force is weak and the structure is loose, which is easy to process.
[0172] Further, prepare 15 parts of calcium chloride and 5 parts of vitamin C, and keep other material components unchanged;
[0173] Prepare a sufficient amount of corn starch and dry it at 70°C for 2 hours, add distilled water to adjust the corn starch into a starch emulsion, add amylase at 60°C and pH=6.0 to enzymolyze the corn starch for 5 hours, add sodium hydroxide solution to adjust the pH of the starch emulsion after enzymolysis to 9.0 and stir and soak for 1 hour, add hydrogen peroxide to the starch emulsion after adjusting the pH, stir it fully, filter and dry the product after the reaction to remove unreacted substances, and obtain modified starch;
[0174] Prepare sufficient amounts of dibutyl adipate and butylene terephthalate copolymer, polybutylene succinate, polycaprolactone, glass fiber, wollastonite, graphite and coupling agent, mix dibutyl adipate and butylene terephthalate copolymer, polybutylene succinate and polycaprolactone in a weight ratio of 5:3:2, put into a twin-screw extruder for mixing, add glass fiber and wollastonite, mix for 2 hours, add graphite and coupling agent, mix for 1.5 hours, obtain modified plastics through extrusion, cooling, pelletizing, washing and drying, and perform quality inspection on the prepared plastics, wherein the temperatures of each zone of the twin-screw extruder (from the feed port to the die outlet) are 160°C, 200°C, 200°C, 220°C, 240°C, 200°C and 190°C;
[0175] Prepare sufficient modified starch, modified plastic, polylactic acid resin, calcium chloride, vitamin C, plasticizer, acetylating agent and lubricant, add appropriate amount of water and amylase to the modified starch, put it in a high-speed mixer, heat it to 80°C, stir it for 10 minutes, add acetylating agent to the gelatinized modified starch, stir it for 20 minutes at a stirring speed of 500 rpm, add plasticizer to the product after the acetylating agent reaction, stir it for 15 minutes, add lubricant to the mixture, stir it for 30 minutes to obtain starch gel, add modified plastic and polylactic acid resin, stir it for 20 minutes, The uniformly mixed mixture is put into a twin-screw extruder for kneading, calcium chloride and vitamin C are added into the twin-screw extruder for kneading, extrusion granulation is performed, the prepared raw materials are put into a pulverizer, processed into granular small materials, the granular small materials are put into a melting machine, the small materials are melted, the melted raw materials are extruded into a film through an extruder, and after cooling and solidification, a shopping bag is obtained, wherein the screw length-diameter ratio of the twin-screw extruder is 48:1, the screw speed is 300 rpm, the temperature of the first zone is 90°C, the temperature of the second zone is 120°C, the temperature of the third zone is 135°C, the temperature of the fourth zone is 120°C, and the temperature of the fifth zone is 90°C.
[0176] Example 4
[0177] See also Figure 1 , Figure 2 and Figure 3 , an environmentally friendly modified starch-based biodegradable shopping bag, comprising the following components in parts by weight: modified starch: 50 parts;
[0178] Modified plastic: 40 parts;
[0179] Polylactic acid resin: 20 parts;
[0180] Calcium chloride: 5 parts;
[0181] Vitamin C: 5 parts;
[0182] Plasticizer: 3 parts;
[0183] Acetyl agent: 2 parts;
[0184] Lubricant: 0.5 parts;
[0185] The calcium chloride changes the thermodynamic parameters of starch gelatinization through polarization to reduce enthalpy change and entropy change. The calcium ions in the calcium chloride form ionic bonds with the hydroxyl groups in the modified starch to form a complex, which can promote the cross-linking reaction between starch molecules and increase the energy required to overcome the hydrogen bond between water molecules and salt ions during starch gelatinization.
[0186] The modified starch comprises the following components in parts by weight: 30 parts of corn starch;
[0187] Hydrogen peroxide: 120 parts;
[0188] Amylase: 7 parts;
[0189] Glycerin: 4 parts;
[0190] Sodium hydroxide solution: 2 parts;
[0191] The oxygen atoms generated by the decomposition of hydrogen peroxide react with hydroxyl groups in the corn starch molecules to convert the hydroxyl groups into carboxyl groups, aldehyde groups and ketone groups;
[0192] The modified plastic comprises the following components in parts by weight: 35 parts of a copolymer of dibutyl adipate and butylene terephthalate;
[0193] Polybutylene succinate: 20 parts;
[0194] Polycaprolactone: 10 parts;
[0195] Glass fiber: 15 parts;
[0196] Wollastonite: 2 parts;
[0197] Graphite: 3 parts;
[0198] Coupling agent: 1 part;
[0199] The glass fiber is short-cut glass fiber and long-cut glass fiber in a weight ratio of 3:1;
[0200] The coupling agent is a phthalate coupling agent and a silane coupling agent;
[0201] The vitamin C can provide electrons to free radicals, interrupt the free radical chain reaction, slow down and hinder the oxidation process of the shopping bag. The vitamin C can clean and remove pigments during the production and processing of the shopping bag by neutralizing the free radicals.
[0202] The weight ratio of the copolymer of dibutyl adipate and butylene terephthalate, polybutylene succinate and polycaprolactone is 5:3:2;
[0203] The wollastonite has a unique needle-like fiber structure, which forms a fiber-reinforced effect during processing. The wollastonite can maintain stable physical and chemical properties at high temperatures. The wollastonite itself does not absorb water, and the thermal expansion absorption of the wollastonite is small and the expansion is linear. When added to plastics, it can prevent the plastics from hygroscopic expansion and expansion cracks from occurring during the heat absorption process of the plastics.
[0204] The graphite is evenly distributed in the modified plastic, and the density of the graphite is 0.85-1.9 g / cm 3The single-layer carbon atom surface of graphite and the layered structure of graphite can prevent the penetration of water molecules. The layers of the layered structure of graphite are combined by the interaction of the instantaneous dipole moment of the molecular crystal. The force is weak and the structure is loose, which is easy to process.
[0205] Further, prepare 5 parts of calcium chloride and 10 parts of vitamin C, and keep other material components unchanged;
[0206] Prepare a sufficient amount of corn starch and dry it at 70°C for 2 hours, add distilled water to adjust the corn starch into a starch emulsion, add amylase at 60°C and pH=6.0 to enzymolyze the corn starch for 5 hours, add sodium hydroxide solution to adjust the pH of the starch emulsion after enzymolysis to 9.0 and stir and soak for 1 hour, add hydrogen peroxide to the starch emulsion after adjusting the pH, stir it fully, filter and dry the product after the reaction to remove unreacted substances, and obtain modified starch;
[0207] Prepare sufficient amounts of dibutyl adipate and butylene terephthalate copolymer, polybutylene succinate, polycaprolactone, glass fiber, wollastonite, graphite and coupling agent, mix dibutyl adipate and butylene terephthalate copolymer, polybutylene succinate and polycaprolactone in a weight ratio of 5:3:2, put into a twin-screw extruder for mixing, add glass fiber and wollastonite, mix for 2 hours, add graphite and coupling agent, mix for 1.5 hours, obtain modified plastics through extrusion, cooling, pelletizing, washing and drying, and perform quality inspection on the prepared plastics, wherein the temperatures of each zone of the twin-screw extruder (from the feed port to the die outlet) are 160°C, 200°C, 200°C, 220°C, 240°C, 200°C and 190°C;
[0208] Prepare sufficient modified starch, modified plastic, polylactic acid resin, calcium chloride, vitamin C, plasticizer, acetylating agent and lubricant, add appropriate amount of water and amylase to the modified starch, put it in a high-speed mixer, heat it to 80°C, stir it for 10 minutes, add acetylating agent to the gelatinized modified starch, stir it for 20 minutes at a stirring speed of 500 rpm, add plasticizer to the product after the acetylating agent reaction, stir it for 15 minutes, add lubricant to the mixture, stir it for 30 minutes to obtain starch gel, add modified plastic and polylactic acid resin, stir it for 20 minutes, The uniformly mixed mixture is put into a twin-screw extruder for kneading, calcium chloride and vitamin C are added into the twin-screw extruder for kneading, extrusion granulation is performed, the prepared raw materials are put into a pulverizer, processed into granular small materials, the granular small materials are put into a melting machine, the small materials are melted, the melted raw materials are extruded into a film through an extruder, and after cooling and solidification, a shopping bag is obtained, wherein the screw length-diameter ratio of the twin-screw extruder is 48:1, the screw speed is 300 rpm, the temperature of the first zone is 90°C, the temperature of the second zone is 120°C, the temperature of the third zone is 135°C, the temperature of the fourth zone is 120°C, and the temperature of the fifth zone is 90°C.
[0209] Example 5
[0210] See also Figure 1 , Figure 2 and Figure 3 , an environmentally friendly modified starch-based biodegradable shopping bag, comprising the following components in parts by weight: modified starch: 50 parts;
[0211] Modified plastic: 40 parts;
[0212] Polylactic acid resin: 20 parts;
[0213] Calcium chloride: 5 parts;
[0214] Vitamin C: 5 parts;
[0215] Plasticizer: 3 parts;
[0216] Acetyl agent: 2 parts;
[0217] Lubricant: 0.5 parts;
[0218] The calcium chloride changes the thermodynamic parameters of starch gelatinization through polarization to reduce enthalpy change and entropy change. The calcium ions in the calcium chloride form ionic bonds with the hydroxyl groups in the modified starch to form a complex, which can promote the cross-linking reaction between starch molecules and increase the energy required to overcome the hydrogen bond between water molecules and salt ions during starch gelatinization.
[0219] The modified starch comprises the following components in parts by weight: 30 parts of corn starch;
[0220] Hydrogen peroxide: 120 parts;
[0221] Amylase: 7 parts;
[0222] Glycerin: 4 parts;
[0223] Sodium hydroxide solution: 2 parts;
[0224] The oxygen atoms generated by the decomposition of hydrogen peroxide react with hydroxyl groups in the corn starch molecules to convert the hydroxyl groups into carboxyl groups, aldehyde groups and ketone groups;
[0225] The modified plastic comprises the following components in parts by weight: 35 parts of a copolymer of dibutyl adipate and butylene terephthalate;
[0226] Polybutylene succinate: 20 parts;
[0227] Polycaprolactone: 10 parts;
[0228] Glass fiber: 15 parts;
[0229] Wollastonite: 2 parts;
[0230] Graphite: 3 parts;
[0231] Coupling agent: 1 part;
[0232] The glass fiber is short-cut glass fiber and long-cut glass fiber in a weight ratio of 3:1;
[0233] The coupling agent is a phthalate coupling agent and a silane coupling agent;
[0234] The vitamin C can provide electrons to free radicals, interrupt the free radical chain reaction, slow down and hinder the oxidation process of the shopping bag. The vitamin C can clean and remove pigments during the production and processing of the shopping bag by neutralizing the free radicals.
[0235] The weight ratio of the copolymer of dibutyl adipate and butylene terephthalate, polybutylene succinate and polycaprolactone is 5:3:2;
[0236] The wollastonite has a unique needle-like fiber structure, which forms a fiber-reinforced effect during processing. The wollastonite can maintain stable physical and chemical properties at high temperatures. The wollastonite itself does not absorb water, and the thermal expansion absorption of the wollastonite is small and the expansion is linear. When added to plastics, it can prevent the plastics from hygroscopic expansion and expansion cracks from occurring during the heat absorption process of the plastics.
[0237] The graphite is evenly distributed in the modified plastic, and the density of the graphite is 0.85-1.9 g / cm 3The single-layer carbon atom surface of graphite and the layered structure of graphite can prevent the penetration of water molecules. The layers of the layered structure of graphite are combined by the interaction of the instantaneous dipole moment of the molecular crystal. The force is weak and the structure is loose, which is easy to process.
[0238] Further, calcium chloride and vitamin C are not added, and other components remain unchanged;
[0239] Prepare a sufficient amount of corn starch and dry it at 70°C for 2 hours, add distilled water to adjust the corn starch into a starch emulsion, add amylase at 60°C and pH=6.0 to enzymolyze the corn starch for 5 hours, add sodium hydroxide solution to adjust the pH of the starch emulsion after enzymolysis to 9.0 and stir and soak for 1 hour, add hydrogen peroxide to the starch emulsion after adjusting the pH, stir it fully, filter and dry the product after the reaction to remove unreacted substances, and obtain modified starch;
[0240] Prepare sufficient amounts of dibutyl adipate and butylene terephthalate copolymer, polybutylene succinate, polycaprolactone, glass fiber, wollastonite, graphite and coupling agent, mix dibutyl adipate and butylene terephthalate copolymer, polybutylene succinate and polycaprolactone in a weight ratio of 5:3:2, put into a twin-screw extruder for mixing, add glass fiber and wollastonite, mix for 2 hours, add graphite and coupling agent, mix for 1.5 hours, obtain modified plastics through extrusion, cooling, pelletizing, washing and drying, and perform quality inspection on the prepared plastics, wherein the temperatures of each zone of the twin-screw extruder (from the feed port to the die outlet) are 160°C, 200°C, 200°C, 220°C, 240°C, 200°C and 190°C;
[0241] Prepare sufficient modified starch, modified plastic, polylactic acid resin, calcium chloride, vitamin C, plasticizer, acetylating agent and lubricant, add appropriate amount of water and amylase to the modified starch, put it in a high-speed mixer, heat it to 80°C, stir it for 10 minutes, add acetylating agent to the gelatinized modified starch, stir it for 20 minutes at a stirring speed of 500 rpm, add plasticizer to the product after the acetylating agent reaction, stir it for 15 minutes, add lubricant to the mixture, stir it for 30 minutes to obtain starch gel, add modified plastic and polylactic acid resin, stir it for 20 minutes, The uniformly mixed mixture is put into a twin-screw extruder for kneading, calcium chloride and vitamin C are added into the twin-screw extruder for kneading, extrusion granulation is performed, the prepared raw materials are put into a pulverizer, processed into granular small materials, the granular small materials are put into a melting machine, the small materials are melted, the melted raw materials are extruded into a film through an extruder, and after cooling and solidification, a shopping bag is obtained, wherein the screw length-diameter ratio of the twin-screw extruder is 48:1, the screw speed is 300 rpm, the temperature of the first zone is 90°C, the temperature of the second zone is 120°C, the temperature of the third zone is 135°C, the temperature of the fourth zone is 120°C, and the temperature of the fifth zone is 90°C.
[0242] Performance Testing
[0243] Test 1: 10 shopping bags prepared in Examples 1-5 were used to test degradation performance according to the soil landfill test in GB / T19275-2003, and the mass loss after 30 days, 60 days and 90 days was calculated;
[0244]
[0245] Test 2: 10 shopping bags prepared in Examples 1-5 were selected, and the degradation performance was tested according to the soil landfill test in GB / T19275-2003 under a humidity of 50%, and the mass loss after 30 days, 60 days and 90 days was calculated;
[0246]
[0247] Test 3: 10 shopping bags prepared in Examples 1-5 were selected, and tensile mechanical properties were tested in the transverse and longitudinal directions according to the GB1040-79 test standard using 4×75 mm dumbbell-shaped pull rods;
[0248]
[0249] Test 4: 10 shopping bags prepared in Examples 1-5 were selected and stored in an environment with a humidity of 50% for 30 days. The horizontal and vertical tensile mechanical properties were tested using 4×75mm dumbbell-shaped pull bars according to the GB1040-79 test standard;
[0250]
[0251]
[0252] Working principle: Calcium chloride changes the thermodynamic parameters of starch gelatinization and reduces enthalpy change and entropy change through polarization phenomenon. Calcium ions in calcium chloride form ionic bonds with hydroxyl groups in modified starch to form complexes, which can promote the cross-linking reaction between starch molecules and increase the energy required to overcome the hydrogen bond between water molecules and salt ions during starch gelatinization. Vitamin C can provide electrons to free radicals, interrupt free radical chain reactions, slow down and hinder the oxidation process of shopping bags. Vitamin C can neutralize free radicals and clean and remove pigments during the production and processing of shopping bags.
[0253] The oxygen atoms produced by the decomposition of hydrogen peroxide in the modified starch react with the hydroxyl groups in the corn starch molecules to convert the hydroxyl groups into carboxyl groups, aldehyde groups and ketone groups. The modified plastic has a unique needle-like fiber structure through wollastonite, which forms a fiber reinforcement effect during processing. Wollastonite can maintain stable physical and chemical properties at high temperatures. Wollastonite itself does not absorb water, and its thermal expansion absorption is small and linear. Adding it to plastics can prevent the plastics from hygroscopic expansion and expansion cracks during the heat absorption process of the plastics. Graphite is evenly distributed in the modified plastics, and the density of graphite is 0.85-1.9g / cm 3 The single-layer carbon atom plane of graphite and the layered structure of graphite can prevent the penetration of water molecules. The layered structure of graphite is combined with each other by the interaction of the instantaneous dipole moment of the molecular crystal. The force is weak, the structure is loose and it is easy to process.
[0254] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. An environmentally friendly modified starch-based biodegradable shopping bag, characterized in that: The invention comprises the following components in parts by weight: 40 to 70 parts of modified starch; Modified plastics: 30 to 50 parts; Polylactic acid resin: 20 to 40 parts; Calcium chloride: 5 to 15 parts; Vitamin C: 5 to 10 parts; Plasticizer: 2 to 8 parts; Acetylating agent: 0.5 to 3 parts; Lubricant: 0.2 to 1 part; The calcium chloride changes the thermodynamic parameters of starch gelatinization and reduces enthalpy change and entropy change through polarization phenomenon. The calcium ions in the calcium chloride form ionic bonds with hydroxyl groups in the modified starch to form a complex, which can promote the cross-linking reaction between starch molecules and increase the energy required to overcome the hydrogen bond between water molecules and salt ions during starch gelatinization.
2. An environmentally friendly modified starch-based biodegradable shopping bag according to claim 1, characterized in that: The modified starch comprises the following components in parts by weight: 30 to 50 parts of corn starch; Hydrogen peroxide: 10 to 30 parts; Amylase: 2 to 10 parts; 1 Glycerin: 2 to 6 parts; Sodium hydroxide solution: 1 to 5 parts; The oxygen atoms generated by the decomposition of hydrogen peroxide react with the hydroxyl groups in the corn starch molecules, converting the hydroxyl groups into carboxyl groups, aldehyde groups and ketone groups.
3. The environmentally friendly modified starch-based biodegradable shopping bag according to claim 1, characterized in that: The modified plastic comprises the following components by weight: 20 to 35 parts of a copolymer of dibutyl adipate and butylene terephthalate; Polybutylene succinate: 20 to 35 parts; Polycaprolactone: 5 to 10 parts; Glass fiber: 10 to 25 parts; Wollastonite: 2 to 8 parts; Graphite: 1 to 5 parts; Coupling agent: 0.5 to 2 parts; The glass fiber is short-cut glass fiber and long-cut glass fiber in a weight ratio of 3:1; The coupling agent is a phthalate coupling agent and a silane coupling agent.
4. The environmentally friendly modified starch-based biodegradable shopping bag according to claim 1, characterized in that: The vitamin C can provide electrons to free radicals, interrupt the free radical chain reaction, slow down and hinder the oxidation process of the shopping bag. Vitamin C can clean and remove pigments during the production and processing of the shopping bag by neutralizing the free radicals.
5. The environmentally friendly modified starch-based biodegradable shopping bag according to claim 3, characterized in that: The weight ratio of the copolymer of dibutyl adipate and butylene terephthalate, polybutylene succinate and polycaprolactone is 5:3:
2.
6. The environmentally friendly modified starch-based biodegradable shopping bag according to claim 3, characterized in that: The wollastonite has a unique needle-like fiber structure, which forms a fiber-reinforced effect during processing. The wollastonite can maintain stable physical and chemical properties at high temperatures. The wollastonite itself does not absorb water, and the thermal expansion absorption of the wollastonite is small and the expansion is linear. Adding it to plastics can prevent the plastics from hygroscopic expansion and expansion cracks during the heat absorption of the plastics.
7. The environmentally friendly modified starch-based biodegradable shopping bag according to claim 3, characterized in that: The graphite is evenly distributed in the modified plastic, and the density of the graphite is 0.85-1.9 g / cm 3 The single-layer carbon atom plane of graphite and the layered structure of graphite can prevent the penetration of water molecules. The layered structure of graphite is combined with each other by the interaction of the instantaneous dipole moment of the molecular crystal. The force is weak, the structure is loose and it is easy to process.
8. A method for preparing an environmentally friendly modified starch-based biodegradable shopping bag, applicable to an environmentally friendly modified starch-based biodegradable shopping bag according to any one of claims 1 to 7, characterized in that: The preparation method of the modified starch is: Step 1: Prepare enough corn starch and dry it in 70℃ environment for 2h; Step 2: Add distilled water to prepare corn starch into starch emulsion; Step 3: adding amylase at 60°C and pH=6.0 to enzymolyze the corn starch for 5 hours; Step 4: adding sodium hydroxide solution to adjust the pH of the enzymatically hydrolyzed starch emulsion to 9.0 and stirring and soaking for 1 hour; Step 5: Add hydrogen peroxide to the starch emulsion after adjusting the pH, and stir thoroughly; Step 6: Filter and dry the product after the reaction to remove unreacted substances to obtain modified starch.
9. The method for preparing an environmentally friendly modified starch-based biodegradable shopping bag according to claim 8, characterized in that: The preparation method of the modified plastic is: Step 1: prepare sufficient amounts of dibutyl adipate-butylene terephthalate copolymer, polybutylene succinate, polycaprolactone, glass fiber, wollastonite, graphite and coupling agent; Step 2: Mix dibutyl adipate, butylene terephthalate copolymer, polybutylene succinate and polycaprolactone in a weight ratio of 5:3:2 and put them into a twin-screw extruder for mixing; Step 3: Add glass fiber and wollastonite and mix for 2 hours; Step 4: Add graphite and coupling agent and mix for 1.5 hours; Step 5: obtaining the modified plastic through extrusion, cooling, pelletizing, washing and drying; Step 6: Conduct quality inspection on the prepared plastic; The temperatures in each zone of the twin-screw extruder (from the feed port to the die outlet) are 160°C, 200°C, 200°C, 220°C, 240°C, 200°C and 190°C.
10. The method for preparing an environmentally friendly modified starch-based biodegradable shopping bag according to claim 8, characterized in that: The preparation method of the environmentally friendly modified starch-based biodegradable plastic bag is as follows: Step 1: Prepare sufficient amounts of modified starch, modified plastic, polylactic acid resin, calcium chloride, vitamin C, plasticizer, acetyl agent and lubricant; Step 2: Add appropriate amount of water and amylase to the modified starch, put it into a high-speed mixer, heat it to 80°C, and stir for 10 minutes; Step 3: adding an acetylating agent to the gelatinized modified starch, and stirring at a stirring speed of 500 rpm for 20 minutes; Step 4: Add plasticizer to the product after adding acetyl agent and stir for 15 minutes; Step 5: Add lubricant to the mixture and stir for 30 minutes to obtain starch gel; Step 6: Add modified plastic and polylactic acid resin and stir for 20 minutes; Step 7: Put the uniformly mixed mixture into a twin-screw extruder for mixing; Step 8: Add calcium chloride and vitamin C into a twin-screw extruder for mixing and extruding into granules; Step 9: Put the prepared raw materials into a crusher and process them into small granular materials; Step 10: Put the granular materials into the melting machine to melt the materials; Step 11: Extruding the melted raw material into a film through an extruder; Step 12: After cooling and solidification, a shopping bag is obtained; The screw length-to-diameter ratio of the twin-screw extruder is 48:1, the screw speed is 300 rpm, the temperature of zone 1 is 90°C, the temperature of zone 2 is 120°C, the temperature of zone 3 is 135°C, the temperature of zone 4 is 120°C, and the temperature of zone 5 is 90°C.
Citation Information
Patent Citations
Preparation method of modified starch-polyvinyl alcohol-based composite plastic film
CN101914223B
A kind of starch-based biodegradable plastic and its preparation method
CN103044718B
Starch-based degradable material and preparation method and application thereof
CN111040392B
A biodegradable composite plastic production process
CN112321903B
Food preparation device
GB2460247A